When Lack of Trust in the Government and in Scientists Reinforces Social Inequalities in Vaccination Against COVID-19 - Bajos, Nathalie; Spire, Alexis; Silberzan, Léna; Sireyjol, Antoine; Jusot, Florence; Meyer, Laurence; Franck, Jeanna-Eve; Warszawski, Josiane; , The EpiCov study group; Bajos, Nathalie; Warszawski, Josiane; Bagein, Guillaume; et al. (Frontiers in Public Health, 2022)
Abstract Objective To assess whether the lack of trust in the government and scientists reinforces social and racial inequalities in vaccination practises Design A follow-up of a random population-based cohort survey. Setting In July 2021, in France. Participants 80,971 participants aged 18 years and more. Main outcome measures Adjusted odds ratios of Covid-19 vaccination status (received at least one dose/ intends to get vaccinated/ does not know whether to get vaccinated/refuses vaccination) were assessed using multinomial regressions to test associations with social and trust factors and to study how these two factors interacted with each other. Results In all, 72.2% were vaccinated at the time of the survey. The population of unvaccinated people was younger, less educated, had lower incomes, and more often belonged to racially minoritized groups, as compared to vaccinated people. Lack of trust of government and scientists to curb the spread of the epidemic were the factors most associated with refusing to be vaccinated: OR=8.86 (7.13 to 11.00) for the government and OR=9.07 (7.71 to 10.07) for scientists, compared to vaccinated people. Lack of trust was more prevalent among the poorer which consequently reinforced social inequalities in vaccination. The 10% poorest who did not trust the government reached an OR of 16.2 (11.9 to 22) for refusing to be vaccinated compared to the 10% richest who did. Conclusion There is a need to develop depoliticised outreach programmes targeted at the most socially disadvantaged groups, and to design vaccination strategies conceived with people from different social and racial backgrounds to enable them to make fully informed choices.